Need of minimal important difference for oral health-related quality of life measures - Masood, M.; Masood, Y.; Saub, R.; Newton, J.T. (2012)
Demand and use for oral health-related quality of life (OHRQoL) instruments have increased in recent years in both research and clinical settings. These instruments can be used to measure patient's health status or detect changes in a patient's health status in response to an intervention or changes in disease trajectory. Ensuring universal acceptance of these measures requires easy interpretation of its scores for clinicians, researchers, and patients. The most important way of describing and interpreting this significance of changes in OHRQoL is through the establishment of minimal important difference (MID). The minimally important difference represents the smallest improvement considered worthwhile by a patient. A comprehensive search of published literature identified only 12 published articles on establishment of MID for OHRQoL measures. This scarcity of published studies on MID encourages the need of appropriate interpretation and describing patient satisfaction in reference to that treatment using MID. Anchor- and distribution-based methods are the two general approaches that have been proposed and recommended to interpret differences or changes in OHRQoL. Both of these methods of determining the MID have specific shortcomings; therefore, it is proposed to adopt triangulation approaches in which the methods are combined. The objective of this review is to summarize the need for, importance of, and recommendations for methods of establishing MID for OHRQoL measures.